The Influence of Motivation and Work Ability on Employee Performance - Indah Fitriany Purwaningtyas; Badia Perizade; Zunaida Zunaida; Marlina Widiyanti (Syntax Corporation Indonesia, 2024)
This research aims to determine the influence of motivation and work ability on employee performance at PT Jasa Marga Toll Road Operator. The population in this research was 150 employees who worked at PT Jasa Marga Toll Road Operator, while the sample in this research used cluster random sampling. So the units selected as samples were not individuals, but organized groups of individuals, where the samples were all 120 operational employees. The results of multiple linear regression analysis show that motivation and work ability have a positive and significant effect on employee performance. For motivation variable, hoped that there will be an opportunity to provide promotions to employees by simplifying the conditions and stages in the consideration and selection process provided. Meanwhile, for the work ability variable, hoped that the Company can become a forum that facilitates employees to improve their abilities. Apart from that, companies also need to provide opportunities for employees to provide input and responses in resolving the problems and challenges.